PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN PENDIDIKAN AL-QUR’AN DI SEKOLAH MENENGAH KEJURUAN NEGERI 1 AMUNTAI KABUPATEN HULU SUNGAI UTARA - AHMAD DZAKY; NOORMINAWATI 01 (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2024)
Merdeka Belajar provides students with the opportunity to study freely and comfortably to study calmly, relaxed and happily without stress and pressure, by paying attention to the natural talents they have, without forcing them to study or master a field of knowledge outside their hobbies and abilities. Differentiated learning is a way for teachers to meet the needs of each student because differentiated learning is a teaching and learning process where students can learn subject matter according to their abilities, what they like and their individual needs so that they do not get frustrated and feel like they have failed in their learning experience.This field research uses a qualitative approach. The results of the research show that: 1) The background for holding differentiated learning in the independent learning curriculum is to meet the needs of different students. 2) The implementation of differentiated learning is carried out with aspects of content, process or product and the implementation of differentiated learning by Al-Qur'an Education Teachers is maximized again. 3) There are various learning media for carrying out differentiated learning as well as assessing independent and group assignments in differentiated learning. 4) Al-Quran Education Teachers have various administrations while student learning outcomes meet the KKTP. 5) Facilities and infrastructure supporting factors, the condition of the learning environment is very adequate in implementing differentiated learning. 6) There are various inhibiting factors in implementing differentiated learning at SMKN 1 Amuntai. 7) The perceived impact of implementing differentiated learning at SMKN 1 Amuntai, both from the school, teachers and students, has a positive impact. 8) There are various solutions provided for the differentiated learning problems experienced by AlQur'an education teachers at SMKN 1 Amuntai. 9) Academic supervision has been carried out by the school principal. 10) The output from implementing differentiated learning both in terms of student understanding and student attitudes has led to better change.